Strategies For Using Canva For Education In Indonesian Language Subjects Creative In Class V MI Mathlaul Huda Tanjungrejo - Afriandi Rifqi, Zakia; Heny Kusmawati (Rayah Al-Islam, 2026)
The use of digital media in advertisement material within the Indonesian language subject is important, as it helps students understand concepts and develop creativity. This study aims to describe teachers’ strategies in utilizing Canva for Education in teaching advertisement material, as well as to identify supporting and inhibiting factors in its implementation. This study employs a qualitative method, with data analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data were collected through interviews, classroom observations, and documentation. The results show that students demonstrate high enthusiasm and engagement in digital-based learning, as materials are presented with attractive designs and students are directly involved in creating advertisement designs. Teachers also find it easier to deliver the material, as it is well-prepared and supported by digital tools. Written evaluations indicate that students understand advertisement concepts and are able to create their own designs through practical activities. The novelty of this study lies in its focus on teachers’ instructional strategies in utilizing Canva for Education and identifying implementation stages along with supporting and inhibiting factors. The policy implication highlights the need for support from stakeholders to optimize digital learning implementation.